Finite element methods for flow problems - Donea, J. (Jean); Huerta, Antonio, 1959- (Chichester : Wiley, 2003)
'The objective [of this book] is to present the fundamentals of stabilized finite element methods for the analysis of steady and time-dependent convection-diffusion and fluid dynamics problems with an engineering rather than a mathematical bias.' -- p. xi.
Includes bibliographical references (p. 323-344) and index
Keywords: Finite element method; Galerkin methods; Fluid dynamics -- Mathematical models